Mengefektifkan Pelaksanaan Supervisi Akademik dalam Upaya Meningkatkan Kompetensi Guru Kelas dalam Proses Pembelajaran di SDN 36 Ampenan - Putu Supatni (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
The purpose of this study is to determine the effectiveness of the implementation of academic supervision in an effort to improve pedagogical competence of classroom teachers in learning in the classroom, the benefits for the principal is to determine the improvement of teacher competence in the learning process. This research was conducted for two cycles, each cycle activity there are four stages of planning, implementation, observation, and reflection. The indicators of success in this study are; 1) School principal observation results and teacher observation during the mentoring process have obtained average score> 4.0, 2) end result> 85% of the number of mentoring participants get average score> 70.00 (good category). The result of the research in cycle I principal principal observation (3.40), average teacher observation (3.17) and academic grade teacher supervision score average (68,56). In cycle II the average principal observation (4.60) with percentage of achievement (100%), average teacher observation (4.50) with percentage of achievement (100%) and academic supervision score average (83, 67) with the percentage of achievement (100%). The success indicator has been reached, the research stated successful and stopped in cycle II. Conclusion; The results of the research on the 2nd cycle showed the improvement of Master's competence in the learning process in the real class. It is recommended that other Principals conduct similar research in an effort to increase the competence of teachers, and to similar class teachers to conduct learning process in accordance with well-planned scenarios, responsibility, bersunggung-sust for the improvement of learning achievement of learners in accordance with the field of study / eyes the lessons he was responsible for.